Gellan gum-based hydrogels for intervertebral disc tissue engineering applications - Silva-Correia, Joana (2011)
Intervertebral disc (IVD) degeneration is a challenging clinical problem that urgently demands viable nucleus pulposus (NP) implant materials. The best suited biomaterial for NP regeneration has yet to be identified, but it is believed that biodegradable hydrogel-based materials are promising candidates. In this work, we have developed ionic- and photo-crosslinked methacrylated gellan gum (GG–MA) hydrogels to be used in acellular and cellular tissue-engineering strategies for the regeneration of IVDs. The physicochemical properties of the developed hydrogels were investigated by Fourier-transform infrared spectroscopy, 1H nuclear magnetic resonance and differential scanning calorimetry. The swelling ability and degradation rate of hydrogels were also analysed in phosphate-buffered saline solution at physiological pH for a period of 30 days. Additionally, the morphology and mechanical properties of the hydrogels were assessed under a scanning electron microscope and dynamic compression, respectively. An in vitro study was carried out to screen possible cytotoxicity of the gellan gum-based hydrogels by culturing rat lung fibroblasts (L929 cells) with hydrogel leachables up to 7 days. The results demonstrated that gellan gum was successfully methacrylated. We observed that the produced GG–MA hydrogels possess improved mechanical properties and lower water uptake ability and degradation rate as compared to gellan gum. This work also revealed that GG–MA hydrogels are non-cytotoxic in vitro, thus being promising biomaterials to be used in IVD tissue-engineering strategies.